The Differences between Dentist’s and Non-Dentist’s Perceptions of Facial Attractiveness - Tanusetiawan, Steffi; Kusnoto, Joko; Yusra, Yohana; Hidayat, Adi (Journal of Dentistry Indonesia, 2016)
Orthodontics plays a role in an individual’s appearance which can affect the perception of others that can vary greatly depending on their educational and social economic background. Objective: To determine if there were differences between dentist’s and non-dentist’s perceptions on facial attractiveness with normal occlusion and various types of malocclusions in Indonesian population. Methods: A cross sectional study was conducted on 80 dentists and 80 non-dentists aged 23-49 years old. The perceptions differences between groups were assessed using visual analogue scale on ten photographs for each gender that have been digitally manipulated. Mann Whitney test was used to analyze the differences. Results: Normal occlusion is the most attractive condition for dentists and non-dentists. There are significant differences between dentist’s and non-dentist’s perceptions of facial attractiveness showing normal occlusion, increased overjet, increased overbite, reduced overjet, reduced overbite, mild crowding, open bite, and reversed overjet malocclusions (p < 0.05). Whilst both groups agreed (p > 0.05) that severe and moderate crowding were the least attractive malocclusion. Conclusion: Regarding the facial attractiveness, dentist’s and non-dentist’s perceptions are significantly different for most malocclusion types. However, there is an agreement that severe and moderate crowding are the most disturbing malocclusion that have a considerable effect on facial attractiveness.